Analysis of Quantum Learning Model with Peer Assessment on Achievement Student’s Critical Thinking Skill in Mathematics - Nurlita, Putri Sandra; Kartono, Kartono; Yulianto, Agus (Journal of Primary Education, 2020)
This research aims to analyze mathematics critical thinking of students on Quantum Learning model with Peer Assessment. This mixed method with sequential explanatory took fifth graders of whole Mayong district, Jepara municipal, in academic year 2018/2019 as the population. The sample consisted of chosen classes: VA and VB. The subjects were six VA students chosen based on three critical thinking groups: high, moderate, and poor. The techniques of collecting data used mathematics critical thinking skill test, peer assessment observation, and interview. The findings showed that Quantum Learning model learning with Peer Assessment was effective to improve mathematics critical thinking skill. On high group category students, they could meet all indicators well. The moderate group students had not been able to meet an indicator, the evaluation. The poor group category students had two unfulfilled indicators, namely evaluation and explanation. Based on the data obtained, it can be concluded that the quantum learning model with peer assessment is effective in improving student’s critical thinking skill in mathematics.